Project development experience in urban environmental infrastructure - Jha, Gangadhar (National Institute of Urban Affairs, 1998)
Papers presented at an International Seminar on Project Development Experience in Urban Environmental Infrastructure, 20-22 April 1998, Pune; with special reference to India and Southeast Asia.